Comparative study of complications of comprehensive neck dissection in primary neck and irradiated neck - Uddin, Md Mosleh; Siddiquee, Belayat Hossain; Rajib, Syed Farhan Ali; Salam, Kazi Shameemus (Bangladesh Journal of Otorhinolaryngology, 2013)
Due to close relationship of vital structures in the neck, certain complications are inherent to neck dissection (ND) for the treatment of patients with metastatic neck disease of squamous cell carcinoma. Aim: To compare the incidence of complications of Comprehensive ND done in primary neck and in irradiated neck. Methods: A cross sectional study of 267 patients with metastatic squamous cell carcinoma in the neck, with or without primary tumor, under gone ND with a curative intension, was made from January 2007 to December 2011 (five years). It was done to identify perioperative complications and to compare them in NDs done in primary neck and in irradiated neck. Result: Total 267 patients with unilateral Comprehensive ND, with or without en-block of the primary tumor, were studied. There was no death. The most frequent complication was marginal mandibular nerve injury (4.05% in primary neck and 8.51% in irradiated neck) followed by intra operative hemorrhage (1.16% in primary neck and 3.19% in irradiated neck). Conclusion: There were no perioperative death in either category; nerves were the most commonly injured structures. Complications were higher in neck dissection in irradiated neck than in primary neck dissection. DOI: http://dx.doi.org/10.3329/bjo.v19i1.14857 Bangladesh J Otorhinolaryngol 2013; 19(1): 5-10